1975
DOI: 10.1111/j.1550-7408.1975.tb05187.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and Electron Microscopic Observations on the Heterotrich Ciliate Climacostomum virens

Abstract: SYNOPSIS. Alveolar membranes and an epiplasm exist under the cell membrane of the noncontractile heterotrich ciliate Climacostomum virens. Postciliary microtubular ribbons join at the right of each somatic kinety to form a Km fiber. Two transverse microtubular fibers occur per kinetosomal pair. A myonemal network interconnects the kinetosomal bases intrakinetally and interkinetally. Ultrastructural comparisons are made between the contractile and noncontractile heterotrichs. The buccal cortex consists of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

1976
1976
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
0
21
0
2
Order By: Relevance
“…Cytochemical studies have not been made but these masses are probably similar to those found in Paramecium (Ehret & Powers, 1955), and for heterotrichs in Blepharisma (Giese, 1973). S. coeruleus does not typically contain the large nucleoli found in another heterotrich, Climacostomum virens (Peck et al 1975).…”
Section: Ultrastrtjcture Of the Macronucleusmentioning
confidence: 99%
“…Cytochemical studies have not been made but these masses are probably similar to those found in Paramecium (Ehret & Powers, 1955), and for heterotrichs in Blepharisma (Giese, 1973). S. coeruleus does not typically contain the large nucleoli found in another heterotrich, Climacostomum virens (Peck et al 1975).…”
Section: Ultrastrtjcture Of the Macronucleusmentioning
confidence: 99%
“…A shedding procedure for the OA, employing urea, and an in vivo ingestion test for RG are presented; both provide a reproducible and well synchronized morphogenetic system for future study. The morphology, ultrastructure, division stomatogenesis, and ingestion in C. virens have been previously reported (7,12,13,23,29).…”
mentioning
confidence: 80%
“…Supported by grants 3.140.77 and 3.657.80 from the Fonds National Suisse de la Recherche Scientifique. 10,000 cells were transferred to a dish (90 mm diameter; 50 mm height) containing 50 ml of Carter's medium (23) and maintained at 26°C. Ciliates were fed daily by giving them enough Chlorogonium to fill each cell without overfeeding (overfeeding results in an abnormal, "bloated" appearance).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations